The Evolving Effect of COVID-19 on the Private Sector - Karalashvili, Nona; Viganola, Domenico (World Bank, Washington, DC, 2021)
This brief provides a descriptive analysis of the evolving effect of the COVID-19 (coronavirus) pandemic on the private sector of 40 countries. It focuses on the essential aspects of business operations: namely, firms' survival, production of goods and services, and jobs. Firms have suffered massive demand and supply shocks, affecting nearly all sectors. These shocks and the consequent drop in revenues have dried up firms' cash flows, depleting their working capital and putting the private sector under considerable financial distress. This brief also examines the effect of the pandemic on firms' liquidity, providing general assessments of the variation of these effects by country income level and firm characteristics. Firms in lower-income countries seem to have been hit harder across several measures, such as declines in sales and the incidence of overdue financial obligations. Within countries, small and medium-sized enterprises (SMEs) with 5 to 99 employees seem to have fared more poorly than large firms. While some signs of a recovery in terms of sales and capacity utilization are emerging, the recovery is fragile, as it bypasses important aspects such as liquidity and job creation. For a full post-pandemic recovery, it is important that sound businesses that are facing a temporary liquidity problem survive, and the workforce rebounds.